New northernmost distribution records of the Eastern South Pacific southern right whale (Eubalaena australis), including the first cases from Ecuador and northern Peru - Castro Ayala, Cristina; García-Cegarra, Ana M.; Uceda-Vega, Piero; Aguilar, Luis; Kelez, Shaleyla; Buchan, Susannah J.; Félix, Fernando; Stack, Stephanie H.; Van Waerebeek, Koen (PloS one, 2024)
The Eastern South Pacific Right Whale (SRW) ( Eubalaena australis ) population has gained interest due to its Critically Endangered conservation status. So far, this population has been confirmed only along the coasts of Chile (18°20’S to 56°30’S) and from southern to central Peru (17°38’S to 12°11’S). Recent records have extended the species’ known range, highlighting its geographic distribution, now reaching 1500 km north. Here, we report six recent records, consisting of five sightings and one stranding, that expand the documented range to northern Ecuador (0.6°N). The northern extension of the population may be associated with the unusual three-year-long cold phase (La Niña) of the El Niño Southern Oscillation (ENSO) in the eastern South Pacific, population expansion, movement and re-distribution of the species, increased monitoring effort, or a combination of these factors. These observations raise hope for the Critically Endangered SRW population, as the occurrence of mother-calf pairs may indicate a potential for population recovery. Nevertheless, these findings intensify concerns for what is still the least abundant SRW population, underscoring the urgency for more targeted research and conservation measures.